Formulasi Granul Effervescent Mengandung Ekstrak Daun Cyclea barbata Miers: Evaluasi Fisik (Sebelum dan Sesudah Rekonstitusi) - Endriyatno, Nur Cholis; Oktavian , Rangga (Journal of Pharmaceutical and Sciences, 2026)
Cyclea barbata Miers leaf extract contains flavonoid compounds that have anti-inflammatory activity. This study aims to determine the effect of variations in citric acid and sodium bicarbonate concentrations on the physical properties of effervescent granules before (organoleptic, flow time, angle of repose, water content, and compressibility index test) and after (organoleptic, dissolve time, foam height, pH, and hedonic) reconstitution. Effervescent granules were formulated using the wet granulation method using varying concentrations of citric acid: sodium bicarbonate, respectively, it is FI (17%: 30%), FII (20%: 27%) and FIII (23%: 24%). Based on the results of the evaluation test of the physical properties of effervescent granules, FI and FII are appropriate for the requirements of each test, while FIII did not appropriate the requirements in the flow time, angle of repose, foam height and pH tests. This study concludes that FI (17%:30%) demonstrated the most optimal physical properties, meeting all evaluation parameters and receiving the highest hedonic score.